Delegation of medication administration from registered nurses to non-registered support workers in community care settings: A systematic review with critical interpretive synthesis. (February 2022) - Shore, Colin B.; Maben, Jill; Mold, Freda; Winkley, Kirsty; Cook, Angela; Stenner, Karen
Abstract: Introduction: Healthcare workforces are currently facing multiple challenges, including aging populations; increasing prevalence of long-term conditions; and shortfall of registered nurses. Employing non-registered support workers is common across many countries to expand service capacity of nursing teams. One task delegated to non-registered support workers is medication administration, which is considered a complex task, with associated risks. This is an important topic given the predicted global increase in patients requiring assistance with medication in community settings. This review explores the evidence on delegation of medication administration from registered nurse to non-registered support workers within community settings, to better understand factors that influence the process of delegation and its impact on service delivery and patient care. Methods: The review followed key principles of Critical Interpretative Synthesis and was structured around Preferred Reporting Items for Systematic Reviews and Meta‐analysis guidelines. Literature searches were conducted in MEDLINE, CINAHL, Embase, and ProQuest-British Nursing Index databases. Twenty studies were included. Results: Findings are reported under four themes: 1, Regulatory and contextual factors; 2, Individual and team level factors; 3, Outcomes of delegation; and 4, Process of implementation and evaluation. Delegation was found to be a complex phenomenon, influenced by a myriad of interconnecting factors at the macro, meso, micro level. At the macro level, the consistency and clarity of government and state level regulations was found to facilitate or impede delegation of medication administration. Lack of clarity at the macro level, impacted at meso and micro levels, resulting in confusion around what medication administration could be delegated and who held responsibility. At the micro level, central to the interpretation of success was the relationship between the delegator and delegatee. This relationship was influenced by personal views, educational and systems factors. Many benefits were reported as an outcome of delegation, including service efficiency and improved patient care. The implementation of delegating medication administration was influenced by regulatory factors, communication, stakeholder engagement, and service champions. Conclusion: Delegation of medication administration is a complex process influenced by many interrelating factors. Due to the increased risk associated with medication administration, clear and consistent regulatory and governance frameworks and procedures are crucial. Delegation of medication administration is more acceptable within a framework that adequately supports the process, backed by appropriate policy, skills, training, and supervisory arrangements. There is a need for further research around implementation, clinical outcomes and medication errors associated with delegation of medication administration.